Global Perspectives on Drug Regulatory Bodies: Roles, Challenges, and Collaborative Frameworks - Ahmed, Rashed (THRIVE Health Science Journal, 2025)
The article "Comparison of Drug Regulatory Bodies: EMA, DGDA, ISO, WHO, TGA, MHRA, and FDA" presents a comprehensive analysis of global drug regulatory organizations, focusing on their roles, responsibilities, and impact on public health. The research delves into the historical development, operational frameworks, and collaborative efforts of these agencies to ensure the safety, efficacy, and quality of pharmaceutical products and medical devices. By incorporating methodologies such as literature review, comparative analysis, critical evaluation, and historical contextualization, the study identifies key similarities and differences among these organizations. The article also examines the critical role of pharmacists in these regulatory bodies, emphasizing their involvement in drug evaluation, pharmacovigilance, and policy development. Furthermore, the study explores the concepts of In-Process Quality Assurance (IPQA) and In-Process Quality Control (IPQC), illustrating their necessity even in the presence of established Quality Control (QC) and Quality Assurance (QA) departments. By addressing challenges such as long approval times, high compliance costs, regulatory inconsistencies, and limited resources in developing countries, the research underscores the importance of global collaboration and regional adaptation in drug regulation. The article concludes by advocating for strengthened regulatory systems, enhanced international cooperation, and balanced approaches to ensure the rational use of drugs and equitable access to quality medicines worldwide.